2023
DOI: 10.3390/biomedicines11051435
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Females in Studies on Antihypertensive Medication over the Years: A Scoping Review

Abstract: Background: The leading global risk factor for cardiovascular-disease-related morbidity and mortality is hypertension. In the past decade, attention has been paid to increase females’ representation. The aim of this study is to investigate whether the representation of females and presentation of sex-stratified data in studies investigating the effect of antihypertensive drugs has increased over the past decades. Methods: After systematically searching PubMed and Embase for studies evaluating the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…Our findings are also consistent with a recent scoping review of antihypertensive medication studies published between 1964 and 2020 that showed substantial underrepresentation of female participants in clinical trials, with only 3.7% of studies stratifying results by sex. 38 Our results are also in keeping with previous work highlighting the underrepresentation of women in cardiovascular and kidney trials. 14 , 38 , 39 , 40 , 41 Pharmacokinetics and pharmacodynamics of drugs differ by sex, 42 which may account for greater AEs and lower adherence in women compared with men using antihypertensive medications, 32 , 33 , 34 , 35 underscoring the importance of reporting sex‐stratified AEs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are also consistent with a recent scoping review of antihypertensive medication studies published between 1964 and 2020 that showed substantial underrepresentation of female participants in clinical trials, with only 3.7% of studies stratifying results by sex. 38 Our results are also in keeping with previous work highlighting the underrepresentation of women in cardiovascular and kidney trials. 14 , 38 , 39 , 40 , 41 Pharmacokinetics and pharmacodynamics of drugs differ by sex, 42 which may account for greater AEs and lower adherence in women compared with men using antihypertensive medications, 32 , 33 , 34 , 35 underscoring the importance of reporting sex‐stratified AEs.…”
Section: Discussionsupporting
confidence: 91%
“… 38 Our results are also in keeping with previous work highlighting the underrepresentation of women in cardiovascular and kidney trials. 14 , 38 , 39 , 40 , 41 Pharmacokinetics and pharmacodynamics of drugs differ by sex, 42 which may account for greater AEs and lower adherence in women compared with men using antihypertensive medications, 32 , 33 , 34 , 35 underscoring the importance of reporting sex‐stratified AEs.…”
Section: Discussionsupporting
confidence: 91%